2017
DOI: 10.1080/00224499.2017.1393494
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for Extradyadic Infidelity Revisited

Abstract: Relationship infidelities are motivated by many distinct factors, with previous research indicating motivations of dissatisfaction, neglect, anger, and sexual desire (Barta & Kiene, 2005). We expand on this by demonstrating additional, empirically distinct motivations for infidelity. Using an Internet-based questionnaire, participants (N = 495), most of whom were young adults, self-reported their infidelities. In addition to evidence for previously studied motivations, our data demonstrate additional factors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 42 publications
2
36
1
7
Order By: Relevance
“…Participants responded to a specific instance of their own infidelity, with items assessing their motives, emotions, and behaviors during their affair. As indicated above, we developed a questionnaire to assess motivations for extradyadic infidelity in a way that allowed for people to indicate possible motives beyond poor relationship health (Selterman et al, 2019).…”
Section: Materials and Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…Participants responded to a specific instance of their own infidelity, with items assessing their motives, emotions, and behaviors during their affair. As indicated above, we developed a questionnaire to assess motivations for extradyadic infidelity in a way that allowed for people to indicate possible motives beyond poor relationship health (Selterman et al, 2019).…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…We reported evidence for 8 statistically distinct infidelity motivation variables: (1) Anger, or feeling upset with a partner's actions, (2) Sexual Desire, or wanting to have more sex, (3) Lack of Love, or feeling an absence of intimacy or affection for a partner, (4) Low Commitment, or not orienting actions around the future of the relationship, (5) Esteem, or a desire for greater autonomy or self-worth, (6) Situation, or clouded judgment due to intoxication or stress, (7) Neglect, or feeling mistreatment from a partner, and (8) Variety, or desiring a greater number of sexual partners. Selterman et al (2019) also reported theoretically consequential associations between these motives and individual difference factors (personality traits and gender identity). For example, sociosexual orientation, which is the degree to which people are comfortable with uncommitted or casual sex (Simpson, Wilson, & Winterheld, 2004), was associated with increased motivation to have an affair because of a desire for sexual variety.…”
mentioning
confidence: 93%
See 3 more Smart Citations